Unveiled - Ekrem, Selma, 1902-1986. (Piscataway, NJ)
xxxi, 320 sayfa, [8] sayfa resim, portre
Keywords: “Selma Ekrem was the granddaughter of Namik Kemal, the Young Ottoman playwright, whose dramatic pleas to reform the empire prompted Sultan Abdnlhamit II to exile him. Growing up among the progressive Ottoman Muslim elite, Ekrem benefited from an unconventional mother, who did not insist on her daughter's veiling. The book covers the family's sojourns outside Istanbul when her father was governor in Jerusalem during the 1908 Young Turk revolution and then governor of the Greek Archipelago Islands, where the whole family was held captive on Mytiline when the island was taken by the Greeks during the Balkan Wars. Returning to Istanbul just as the First World War broke out, Ekrem attended the American College for Girls where she was one of a growing number of Muslim students. Unveiled provides a commentary on how the school's inclusive multi-ethnic studentship found itself newly divided by the split loyalties of the First World War, the Allied occupation, and the Greek invasion. Frustrated at the restrictions of Turkish female life (though a strong supporter of Mustafa Kemal), Ekrem traveled to America and earned a living giving lectures on Turkey, which countered prevalent Orientalist stereotypes“ -- Yayıncı.